Awe, the diminished self, and collective engagement Universals and cultural variations in the small self. [article]. - Bai, Young; Maruskin, Laura
Awe has been theorized as a collective emotion, one that enables individuals to integrate into social collectives. In keeping with this theorizing, we propose that awe diminishes the sense of self and shifts attention away from individual interests and concerns. In testing this hypothesis across 6 studies (N = 2137), we first validate pictorial and verbal measures of the small self; we then document that daily, in vivo, and lab experiences of awe, but not other positive emotions, diminish the sense of the self. These findings were observed across collectivist and individualistic cultures, but also varied across cultures in magnitude and content. Evidence from the last 2 studies showed that the influence of awe upon the small self accounted for increases in collective engagement, fitting with claims that awe promotes integration into social groups. Discussion focused on how the small self might mediate the effects of awe on collective cognition and behavior, the need to study more negatively valenced varieties of awe, and other potential cultural variations of the small self. -- (from the authors)